Elements of a theory of global governance. (November 2016) - Held, David
In the aftermath of the Second World War the international institutional breakthroughs that occurred provided the momentum for decades of sustained economic growth and geopolitical stability sufficient for the transformation of the world economy, the shift from the cold war to a multipolar order, and the rise of new communication and network societies. However, what worked then does not work as well now, as gridlock freezes problem-solving capacity in global governance. The search for pathways through and beyond gridlock is a hugely significant task – nationally and globally – if global governance is to be once again effective, responsive and fit for purpose. This article explores these issues and provides elements of a theory of global governance in order to begin to understand the challenges of the 21st century and how to surmount them.